Pressure Changes During Layer Cupping in a Skin Model - Dong Wook Shim; Soo Kwang An; Ha Lim Lee; Jae Yong Lee; Byung Ryul Lee; Gi Young Yang (MEDrang Inc., 2021)
Background Cupping is widely used in Korean medicine, but there is a risk of bacterial infection if the suction pump (used for inducing negative pressure) and the patients' skin are not separated. This study aimed to investigate the effect of layer cupping by comparing the pressure changes between layer cupping and conventional cupping. Methods To evaluate pressure changes the study was designed with 3 types of conditions applied to a skin model: (1) a Dongbang cup with a manual or motor suction pump (conventional cupping); (2) layer cupping with 2 Dongbang cups; and (3) layer cupping with a cup made by 3D printing and a Dongbang cup. Results When a manual suction pump was used (conventional cupping), the pressure did not decrease steadily, and in 1 section there was an increase in pressure. When layer cupping was used, the pressure in the lower cup (which would be directly applied to the patient's skin), decreased steadily. Conclusion In the pressure change graph for layer cupping in this skin model, the pressure in the lower cup (which would be placed on the patient's skin) steadily decreased, and reached equilibrium. Therefore, the layer cupping model may help to reduce the risks of bacterial infection.